Design and Characterization of Various Lipid, Polymer, and Gemini-Surfactant – Based Vectors and DNA as Non-Viral Delivery Systems for Gene Therapy Applications - Lall, Gurmeet Kaur (University of Waterloo, 2023)
The bulk of this thesis work is the result of a pharmaceutical collaboration, and it utilizes several proprietary systems. While Chapters 3 and 4 will provide an in-depth discussion of the results, the specific names, structures, and manufacturing processes of the systems cannot be disclosed. Genes are segments of DNA – the blueprint of all living organisms which contain instructions needed for organisms to grow, survive, and reproduce. However, genes that do not function properly can cause various diseases and genetic defects. Gene therapy has the potential to treat these diseases by correcting the underlying genetic problem. Recent success with the use of lipid nanoparticles have demonstrated that gene delivery by using synthetic vectors is effective and commercially achievable. However, other synthetic carriers, such as polymers and gemini surfactants (GS), continue to face challenges associated to low gene expression which limits their clinical application. The rational design approach, where individual vector components are selected based on favourable transfection efficiency properties, is often used in non-viral formulation development. Countless studies have used this approach to focus on designing efficient synthetic carriers. However, highly efficient non-viral gene therapeutics require the rational design of all components of the vector – namely the synthetic carrier and the DNA cargo. For example, to address the several challenges associated with the use of conventional circular covalently closed (CCC) plasmid DNA (pDNA) vectors, a new generation of DNA vectors have been under investigation, linear covalently closed (LCC) DNA minivectors. Although preliminary studies have shown that the in vitro transfection efficiency of formulations incorporating the LCC DNA minivectors is higher compared to formulations incorporating the CCC DNA counterpart, their overall transfection efficiencies still appear to be limited. Key to improving their efficiency is characterizing both the synthetic carrier and the DNA construct and to establish a relationship between molecular interactions, physicochemical properties, and transfection. This approach may optimize LCC DNA minivector-based formulations for future non-viral gene therapy applications. In collaboration with a pharmaceutical partner, we designed a study to assess the influence of DNA size and topology on physicochemical properties (i.e. size, polydispersity index (PDI), and zeta potential) and in vitro transfection efficiency. Cationic lipids (Lipofectamine 3000 and proprietary Lipid 2) complexed with either the proprietary LCC DNA minivectors or CCC pDNA in deionized water were prepared and evaluated. Comparable physicochemical properties were observed despite the differences in DNA size and topology. Sizes of all lipoplexes were below 325 nm and the positive zeta potentials appeared to increase linearly with increasing N+/P- ratio. Transfection efficiency was evaluated by expression of enhanced green florescence protein (eGFP) in HEK 293 and ARPE-19 cells in vitro, and cell viability was determined by propidium iodide staining. Statistically significant increases in transfection efficiency were observed with samples prepared with the LCC DNA minivectors and higher overall transfection was associated with Lipofectamine 3000/LCC DNA minivector lipoplexes as determined by one-way analysis of variance (ANOVA) and a dependent, two-tailed, two sample Student’s t-test (same results obtained by both methods). These findings reveal that a relationship between DNA size, topology, and transfection efficiency exists and should be considered for effective cationic lipid/LCC DNA minivector lipoplex design and formulation development. In an effort to improve the transfection efficiencies of LCC DNA minivectors for non-viral gene therapy, the relationship between physicochemical properties and transfection efficiency of polymer-LCC DNA minivectors were studied. Formulations comprising the proprietary Polymer 1 or proprietary Polymer 2 incorporating either LCC DNA minivectors or CCC pDNA in deionized water were prepared at several N+/P- ratios (2:1, 4:1, and 8:1) and their physicochemical properties (size, zeta potential, and PDI), transfection efficiency (eGFP expression), and cell viability (determined by propidium iodide staining) were evaluated. Higher transfection was achieved with polyplexes forming small (< 150 nm), uniformly distributed (PDI < 0.2) nanoparticles with an excess positive charge (zeta potential ~ 25 mV), presumably due to high cell interactions and internalization. The link to transfection efficiency found from this study may contribute to the rational design and optimization of future LCC DNA minivector-based polyplexes. To briefly provide insight into the low gene expression of GS-DOPE-LCC DNA minivector systems previously determined by our group, the mixing behaviour and interactions between DOPE and two GS (18-7-18 or 18-7NH-18) were characterized at pH 4 and pH 7 at various ratios using Langmuir monolayer methods. The mixing behaviours were derived from π–A curves by examining the excess free energy of mixing (ΔGE) which was calculated through the surface area additivity rule, while the intermolecular interactions of the mixtures were evaluated using the compressibility modulus (Cs-1). Synergistic interactions dominated in most binary mixtures, with the exception of XGS = 0.5 monolayers where a net repulsive force was dominant. This synergism may explain the low gene expression of GS-DOPE-LCC DNA minivectors, as it may attribute to low LCC DNA release from the vector. These findings may be used for future optimization.
Keywords: Lipids; Polymers; Gemini surfactants; Linear DNA minivectors; Circular plasmid DNA; Non-viral vectors; Gene delivery; Gene therapy; Physicochemical characterization; In vitro transfection; Langmuir monolayer methods